In situ observation of rolling contact fatigue cracks by laminography using ultrabright synchrotron radiation (Fracture and Structural Integrity, 2015)
In rolling contact fatigue (RCF), cracks usually initiate from inclusions beneath the surface andpropagate to the contact surface. In the present study, synchrotron radiation computed laminography (SRCL)imaging was performed to observe flaking defects during the RCF of a high-strength steel. Specially fabricatedinclusion-rich steel plate specimens were employed in the experiments. For the in situ observation of crackpropagation, a compact RCF testing machine was developed, and a 4D analysis scheme was applied to the dataobtained by SRCL. RCF tests were carried out near the measurement hatch of the beam line used SRCL toenable the successive observation of crack initiation and growth behaviors. Specimens before and after theoccurrence of flaking were observed by SRCL, and flaking defects and cracks under the surface weresuccessfully detected. As a result, details of the crack initiation and flaking process in RCF could be discussed.Shear-type horizontal cracks were found to initiate after the initiation and propagation of tensile-type verticalcracks along inclusions, where the face of the vertical cracks was perpendicular to the rolling direction androlling surface. Therefore, the formation of vertical cracks is considered to affect shear-type crack formationand flaking, where the shape and length of inclusions also affect the initiation and propagation of verticalcracks.
Keywords: Rolling contact fatigue